Subgroups of direct products of two limit groups - Bridson, MR; Howie, J (International Press, 2007)
If Γ1 and Γ2 are limit groups and S ⊂ Γ1 × Γ2 is of type FP2 then S has a subgroup of finite index that is a product of at most two limit groups.